Inhibition of NADPH oxidase within midbrain periaqueductal gray decreases pain sensitivity in Parkinson's disease via GABAergic signaling pathway - Zhang, W; Sun, L; Yang, X; Wang, R; Wang, H (Physiological research, 2020)
Hypersensitive pain response is observed in patients with Parkinson's disease (PD). However, the signal pathways leading to hyperalgesia still need to be clarified. Chronic oxidative stress is one of the hallmarks of PD pathophysiology. Since the midbrain periaqueductal gray (PAG) is an important component of the descending inhibitory pathway controlling on central pain transmission, we examined the role NADPH oxidase (NOX) of the PAG in regulating exaggerated pain evoked by PD. PD was induced by central microinjection of 6-hydroxydopamine to lesion the left medial forebrain bundle of rats. Then, Western Blot analysis and ELISA were used to determine NOXs and products of oxidative stress (i.e., 8-isoprostaglandin F2alpha and 8-hydroxy-2'-deoxyguanosine). Pain responses to mechanical and thermal stimulation were further examined in control rats and PD rats. In results, among the NOXs, protein expression of NOX4 in the PAG of PD rats was significantly upregulated, thereby the products of oxidative stress were increased. Blocking NOX4 pathway in the PAG attenuated mechanical and thermal pain responses in PD rats and this was accompanied with decreasing production of oxidative stress. In addition, inhibition of NOX4 largely restored the impaired GABA within the PAG. Stimulation of GABA receptors in the PAG of PD rats also blunted pain responses. In conclusions, NOX4 activation of oxidative stress in the PAG of PD rats is likely to impair the descending inhibitory GABAergic pathways in regulating pain transmission and thereby plays a role in the development of pain hypersensitivity in PD. Inhibition of NOX4 has beneficial effects on the exaggerated pain evoked by PD.
Keywords: fasciculus telencephali medialis; Medial Forebrain Bundle; modely nemocí na zvířatech; Male; pyridony; potkani Sprague-Dawley; GABA; NADPH Oxidase 4; práh bolesti; signální transdukce; Pain; NADPH-oxidasa 4; mužské pohlaví; Periaqueductal Gray; Signal Transduction; Pyridones; Pyrazolones; krysa rodu Rattus; substantia grisea centralis; bolest; Animals; zvířata; Rats; Disease Models, Animal; pyrazolony; Pain Threshold; Parkinson Disease; Parkinsonova nemoc; gamma-Aminobutyric Acid; Rats, Sprague-Dawley